(untitled) (Research, Society and Development, 2024)
The use of polymethylmethacrylate (PMMA) in aesthetic clinical practice has been the subject of growing interest and debate, due to its applicability in facial rejuvenation procedures and correction of bone defects. Recognized for its durability, biocompatibility, and versatility. PMMA is often used for facial filler and orofacial harmonization. However, concerns regarding complications and regulations have also arisen. In this sense, the objective of this study was to conduct an integrative review of the literature in order to comprehensively analyze the applications, complications and regulatory aspects of PMMA in aesthetic clinical practice. To achieve this purpose, the databases of Google Scholar, LILACS and SciELO were consulted, covering the period from 2018 to 2024. Throughout the review, several types of studies were identified, including narrative reviews, systematic reviews, and observational studies. PMMA has been widely used in the aesthetic sphere, due to its properties of biocompatibility, mechanical stability and absence of toxicity, color, taste and odor. This compound has been shown to be used in several areas of aesthetic medicine, such as transplants and prostheses, ophthalmology, dentistry and aesthetic tissue correction. However, serious complications associated with its use have also been observed, such as fat embolism, hypercalcemia, chronic kidney disease, and formation of granulomas and nodules, resulting in edema, erythema, lymphedema, and tissue necrosis. In addition, regulatory concerns were identified, including the lack of standardization of procedures and the absence of clear guidelines for the use of PMMA in clinical practice in the field of aesthetics.